The contributions of public health policies and healthcare quality to gender gap and country differences in life expectancy in the UK - Kasim Allel; Franceso Salustri; Hassan Haghparast-Bidgoli; Ali Kiadaliri (BMC, 2021)
Abstract Background In many high-income countries, life expectancy (LE) has increased, with women outliving men. This gender gap in LE (GGLE) has been explained with biological factors, healthy behaviours, health status, and sociodemographic characteristics, but little attention has been paid to the role of public health policies that include/affect these factors. This study aimed to assess the contributions of avoidable causes of death, as a measure of public health policies and healthcare quality impacts, to the GGLE and its temporal changes in the UK. We also estimated the contributions of avoidable causes of death into the gap in LE between countries in the UK. Methods We obtained annual data on underlying causes of death by age and sex from the World Health Organization mortality database for the periods 2001-2003 and 2014-2016. We calculated LE at birth using abridged life tables. We applied Arriaga's decomposition method to compute the age- and cause-specific contributions into the GGLE in each period and its changes between two periods as well as the cross-country gap in LE in the 2014-2016 period. Results Avoidable causes had greater contributions than non-avoidable causes to the GGLE in both periods (62% in 2001-2003 and 54% in 2014-2016) in the UK. Among avoidable causes, ischaemic heart disease (IHD) followed by injuries had the greatest contributions to the GGLE in both periods. On average, the GGLE across the UK narrowed by about 1.0 year between 2001-2003 and 2014-2016 and three avoidable causes of IHD, lung cancer, and injuries accounted for about 0.8 years of this reduction. England & Wales had the greatest LE for both sexes in 2014-2016. Among avoidable causes, injuries in men and lung cancer in women had the largest contributions to the LE advantage in England & Wales compared to Northern Ireland, while drug-related deaths compared to Scotland in both sexes. Conclusion With avoidable causes, particularly preventable deaths, substantially contributing to the gender and cross-country gaps in LE, our results suggest the need for behavioural changes by implementing targeted public health programmes, particularly targeting younger men from Scotland and Northern Ireland.